EVALUATION OF IMMIGRATION AREA STANDARDIZATION POLICY AT ARUK PLBN - Faiz, Muhammad (Journal of Administration and International Development, 2022)
Based on the Minister of Law and Human Rights Regulation Number 44 of 2015 concerning procedures for checking entry and exit of Indonesian territory, which includes discussing facilities and infrastructure in the immigration area. The results of observations related to facilities and infrastructure for the implementation of immigration checks at TPI Aruk are not in accordance with Permenkumham Number 44 of 2015. Because facilities and infrastructure are an important element in supporting immigration checks. So this study discusses the evaluation of existing facilities and infrastructure at TPI Aruk. This study aims to evaluate the standard policy of the immigration area at the Aruk TPI as well as efforts to improve immigration services. This study uses a descriptive method with a qualitative approach where humans are the main actors in determining the results of writing which are described through words or statements according to the circumstances that occur. The results of this study indicate that the existing facilities and infrastructure are not in accordance with Permenkumham Number 44 of 2015 and also the layout of the immigration area is not strategic, causing immigration checks to not run optimally.